Revision of the genus Omalaspis Giraud, 1860 (Hym.: Figitidae: Aspicerinae) - Ros-Farré, P.; Pujade-Villar, J. (Zootaxa, 2011)
Omalaspis Giraud, 1860, is a genus of Aspicerinae (Hymenoptera: Cynipoidea: Figitidae) with a Holarctic distribution. The diagnostic characters that differentiate Omalaspis from morphologically similar genera are described. From the thirteen known species of Omalaspis only O. cavroi (Hedicke, 1914), O. latreillii (Hartig, 1840), O. norica Giraud, 1860 and O. orientalis Belizin, 1968 are valid species. All these species are redescribed. Omalaspis nigra (Hartig, 1840) and O. abnormis (Kieffer, 1901) are synonymized with O. norica, and O. ruficornis Thomson, 1877 is synonymized with O. latreilli. Omalaspis laevis Hedicke, 1914 belongs to Xyalaspis, O. davydovi Belizin, 1927 is considered as ‘incertae sedis’ and O. carinata (Kieffer 1901) ‘species dubia’. Three species are considered as species inquirenda: Omalaspis femoralis Ionescu, 1963 (which belongs to Diapriidae), O. convexa Kierych, 1985 and O. sulcata (Kieffer, 1901). Six new species are described: O. asiatica Ros-Farré & Pujade-Villar n. sp., O. brandaoi Pujade-Villar & Ros-Farré n. sp., O. curvilineata Ros-Farré & Pujade-Villar n. sp., O. gibsoni Ros-Farré & Pujade-Villar n. sp., O. niponica Ros-Farré & Pujade-Villar n. sp. and O. villemantae Pujade-Villar & Ros-Farré n. sp. The diagnostic characters of all species are illustrated and a key to differentiate them is given. A new character is defined here exclusive to Omalaspis within the Aspicerinae, the supratorular impression.